The Mediating Role of Village Funds in the Relationship Between Poverty Rate and Economic Growth in Sumatra, Indonesia - Rahmi Raihan; Lianti Lianti; Fakriah Fakriah; Yeni Irawan (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
This study examines the effectiveness of Village Funds in reducing poverty and promoting economic growth across districts and cities on Sumatra Island, Indonesia. It aims to analyze both the direct and indirect effects of Village Funds on poverty rates and village economic growth using a comprehensive panel dataset from 2018 to 2023. The study applies Structural Equation Modeling (SEM) to explore the mediating role of poverty in the relationship between Village Funds and economic growth, offering new insights into the impact of fiscal decentralization on rural development. Using a quantitative panel data approach with 689 observations from 121 districts and cities, the results indicate that Village Funds significantly enhance village economic growth but do not directly reduce poverty. Poverty rates negatively influence economic growth and partially mediate the relationship between Village Funds and economic growth, though this mediation is not statistically significant. The findings emphasize that the developmental benefits of Village Funds depend on governance quality, fund management, and community engagement. The study provides valuable guidance for policymakers to strengthen institutional capacity and improve fund targeting, supporting inclusive and sustainable rural development.